Estudio del perfil psicológico de Víctimas que asisten a la Comisaría Segunda de la Mujer y la Familia de la Ciudad de Quito - Gómez Coronel, María Belén (2009)
Violence against women by husbands, uncles, romantic partners, among others cover a number of aggressive both psychological and physical, harassment, sexual abuse, and even murder. This shows a grim reality in our country and the world. The following work was based on several questions, one of which, why the victim continues her victimizer, and what type of care is given to the victim and the victimizer?, Answers revolve around hypothesis so learned about violence along the popular myths career, so it was decided to set up an investigation singular in the Second Precinct of Women and the Family of Quito.